If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -9 = x + 7 Reorder the terms: -9 + 9x = x + 7 Reorder the terms: -9 + 9x = 7 + x Solving -9 + 9x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -9 + 9x + -1x = 7 + x + -1x Combine like terms: 9x + -1x = 8x -9 + 8x = 7 + x + -1x Combine like terms: x + -1x = 0 -9 + 8x = 7 + 0 -9 + 8x = 7 Add '9' to each side of the equation. -9 + 9 + 8x = 7 + 9 Combine like terms: -9 + 9 = 0 0 + 8x = 7 + 9 8x = 7 + 9 Combine like terms: 7 + 9 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| d-10=-18 | | -8x-15=7x+15 | | 0.50x+0.45(70)=33.5 | | 4x=30+7 | | -12=5m+68 | | 2x-6=10-2x | | 4x-20=52 | | 3.4x=12 | | 6x+3y=5 | | 5x+14=3+7x-9 | | 2t^2-2t=0 | | 3-8*n=n | | 5x-1-6(x-1)=5x-4 | | 22-6x=92 | | 5x=-225 | | 2t-3=9-4t | | x+3x=1280 | | 19m-3=7-m | | 1.6m=10 | | 4x=-32 | | -7x+12y=4 | | 3y+x=6 | | x^2+16x+96=0 | | 4t^2-7t=1 | | 2x=6x+7 | | (x-6)(x-7)=0 | | 6x-9=-15 | | 4x-6y=18 | | 5-8b=-3b-5(5+2b) | | 35y-60x=72 | | 2+7k=-k+20 | | -2x=100+18x |